Dominica : Technical Assistance Report-External Sector Statistics. (IMF Staff Country Reports; Country Report, 2022)
A remote technical assistance (TA) mission on external sector statistics (ESS) was conducted to the Statistics Department of Dominica (SDD) during August 30 to September 10, 2021. The mission was carried out as part of the Caribbean Regional Technical Assistance Centre (CARTAC) work program on ESS. The balance of payments and international investment position (IIP) statistics for Dominica are compiled jointly by the SDD and the Eastern Caribbean Central Bank (ECCB).1 In this context, three staff from the ECCB participated in the mission in their capacity of ESS compilers for Dominica. Fadhila Alfaraj of the IMF's Statistics Department (STA) joined the mission.